2014
DOI: 10.1001/jamapsychiatry.2014.1031
|View full text |Cite
|
Sign up to set email alerts
|

Reward Processing in Healthy Offspring of Parents With Bipolar Disorder

Abstract: IMPORTANCE Bipolar disorder (BD) is highly familial and characterized by deficits in reward processing. It is not known, however, whether these deficits precede illness onset or are a consequence of the disorder.OBJECTIVE To determine whether anomalous neural processing of reward characterizes children at familial risk for BD in the absence of a personal history of a psychopathologic disorder. DESIGN, SETTING, AND PARTICIPANTSThis study compared neural activity and behaviors of children at high and low risk fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 64 publications
3
56
1
Order By: Relevance
“…BOLD images were registered to the high-resolution structural images using FLIRT; the high-resolution images were registered to the MNI152_T1_2mm template, as in previous neuroimaging studies of youth with age ranges comparable to that in the present study (Burgund et al 2002;Kang et al 2003;Singh et al 2013, 2014;Bebko et al 2014;Olsavsky et al 2014), using FNIRT, and the two resulting transformations were concatenated and applied to the original BOLD image to transform it to MNI space. The registration quality was checked for each subject.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BOLD images were registered to the high-resolution structural images using FLIRT; the high-resolution images were registered to the MNI152_T1_2mm template, as in previous neuroimaging studies of youth with age ranges comparable to that in the present study (Burgund et al 2002;Kang et al 2003;Singh et al 2013, 2014;Bebko et al 2014;Olsavsky et al 2014), using FNIRT, and the two resulting transformations were concatenated and applied to the original BOLD image to transform it to MNI space. The registration quality was checked for each subject.…”
Section: Methodsmentioning
confidence: 99%
“…Only one previous study compared neural underpinnings of reward processing in BO vs. HC (Singh et al 2014). This study showed elevated vlPFC activity and altered vlPFC-ACC functional connectivity during reward processing in healthy BO vs. HC (Singh et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…No additional article was found in the manual search. Most of the studies were conducted in adolescents [23][24][25][26][27][28][29][30] with only two studies conducted in young adults [31,32]. The samples of subjects at-risk for BD were comprised of healthy offspring of bipolar patients [25,28,29], healthy and symptomatic offspring of bipolar patients [24,26,27,30], symptomatic offspring of bipolar patients [23] and healthy and symptomatic offspring or siblings of bipolar patients [31,32].…”
Section: Study Selectionmentioning
confidence: 99%
“…The samples of subjects at-risk for BD were comprised of healthy offspring of bipolar patients [25,28,29], healthy and symptomatic offspring of bipolar patients [24,26,27,30], symptomatic offspring of bipolar patients [23] and healthy and symptomatic offspring or siblings of bipolar patients [31,32]. Some studies were conducted by the same research groups, with partially overlapping samples [23,26,27,30] The studies focused in 4 functional imaging domains: 2 studies employed an emotion processing task [23,26]; 2 studies employed a cognitive-affective task [25,31]; 3 studies employed a reward processing task [27,28,30] and 3 were resting state fMRI studies [24,29,32]. Table 1 resume the main methodological characteristics and results of the selected studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation